Dedicated Assessors: description of an innovative education intervention to facilitate direct observation in the clinical setting - Acker, Amy; Hawksby, Emily; MacPherson, Peter; Leifso, Kirk (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Background: The Department of Pediatrics at Queen’s University undertook a pilot project in July 2017 to increase the frequency of direct observations (DO) its residents received without affecting the patient flow in a busy hospital-based pediatric ambulatory care clinic. Facilitating DO for authentic workplace-based assessments is essential for assessing resident’s core competencies. The purpose of this study was to pilot an innovative education intervention to address the challenge of implementing DO in the clinical setting.Methods: The project allowed for staff physicians to act as “dedicated assessors” (DA), a faculty member who was scheduled to conduct direct observations of trainees’ clinical skills, while not acting as the attending physician on duty. At the end of the project, focus group interviews were conducted with faculty and residents, and thematic analysis was completed.Results: Participants reported an increase in the overall quality of feedback received during the observations performed by a DA, with more specific feedback and a broader focus of assessment. There seemed to be little disruption to patient care. Some residents described the observations as anxiety-provoking.Conclusions: Overall, this project provides insight into an educational approach that medical residency programs can apply to increase the frequency of workplace-based DO and boost the quality of feedback residents receive while maintaining the flow of already busy ambulatory care clinics.